Stripping voltammetric measurements of Cd(II) and Pb(II) analytical signals at mercury-graphite electrode - A. M. Lebedev; A. I. Kamenev; A. A. Ischenko (Тонкие химические технологии, 2011)
The results of Cd(II) and Pb(II) signals measurement at mercury-graphite electrodes upon the formation (changing coatings) and those of investigated solutions were compared. Trace amounts of depolarizers were found in samples of treated waste water.